Use-wear analysis of copper-alloy artifacts. A window of opportunity or a dead end? - Kasprowicz, Marcin (Folia Praehistorica Posnaniensia, 2022)
A world seen through the lenses of a microscope can lead to exceptional discoveries. Regarding archaeology, it can grant us knowledge about the possible usage of certain artifacts in the past. Previously unrecognized and unclassified fragments of flint and bone can be reinterpreted as a completely different item. Throughout the years there were a small few astounding scientist who laid foundations and improved on this part of archaeology. In this already tight-knit group of researchers there is an even smaller group of people who are interested in applying use-wear analysis to copper-alloy artifacts. It is quite a different approach. You still look for signs of usage or any other traces but the difference in material and overall structure of an artifact makes for quite a difficult task. The multiple issues and setbacks such as corrosion, acidity of the soil, the composition of alloys, conservation or simple mismanagement of an artifact can lead to a lot of misleading conclusions. Despite all those problem you can still gather data from use-wear analysis on metal. But can it be used in forming any sort of narrative or is just a “collection of pretty pictures”?